Uniformity in The Legislative Process Following Constitutional Court Rulings - Arief Fahmi Lubis; Parluhutan Sagala; Tetty Melina Lubis (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
Constitutional Court rulings are final and binding, having a direct impact on the validity of existing legal regulations. This study aims to highlight the lack of uniformity in the legislative steps taken after Constitutional Court decisions. Employing a qualitative, descriptive approach, the research systematically collects data to provide an accurate and timely representation of the current legislative context. The findings reveal that the inconsistency in legislative processes following Constitutional Court rulings contributes to legal uncertainty, underscoring the necessity for standardized procedures in the legislative follow-up.